Containerization and Orchestration: Implementing OpenShift and Docker - Sowmith Daram; Prof.(Dr.) Arpit Jain; Er. Om Goel (Innovative Research Thoughts, 2021)
Containerization and orchestration have revolutionized the deployment and management of applications, offering unprecedented levels of efficiency, scalability, and consistency. This paper delves into the intricacies of implementing two leading technologies in this domain: Docker for containerization and OpenShift for orchestration. Docker has emerged as a foundational tool that packages applications and their dependencies into portable containers, enabling consistent execution across various environments. Meanwhile, OpenShift, a Kubernetes-based platform, extends Docker’s capabilities by providing robust tools for container orchestration, application deployment, and scaling. The paper explores the architectural components of Docker and OpenShift, emphasizing how they complement each other to form a comprehensive solution for modern application management. It highlights the benefits of using Docker containers, such as lightweight execution, isolation, and ease of integration into CI/CD pipelines. Moreover, it discusses OpenShift’s orchestration capabilities, including automated scaling, load balancing, and self-healing, which are essential for maintaining high availability and performance in dynamic environments.